Investigation of Genetic-molecular Sources of Multidrug Resistance of Salmonella Isolated from Eggs - Mohammad Saram; Arash Chaichi Nosrati; Leila Modiri; Khossrow Issazadeh (Shahid Beheshti University of Medical Sciences, 2022)
Background: Bacteria can be transmitted to consumers around the world due to the movement of animals, and food products. One of the most important sources of Salmonella transmission to humans is through eggs. Methods: 500 egg samples from 37 Iranian brands were extracted from Salmonella yolk and shell source and after confirmation by differential phenotypic methods and resistance test for tetracycline, cellophanamide and nitrofurantoin-furazolidone antibiotics were performed. DNA of strains was extracted and using PCR with specific primers, the presence of tetA, tetB, tetC, tetD, tetG, tetE, tetE, tetH, sul (I), sul (II), sul (III), nfsA, nfsB were examined according to control DNA (ATCC14028). Results: Among the genes of teta, tetb.tetc, tetd, tete, tetf, tetg and teth, the presence of tetc was seen in 81% of the samples and not in 19% of them. Other tetracycline resistance genes were not found in the samples. Tracing of genes related to sulfonamide resistance by PCR showed that among the Sul1, Sul2, and Sul3 genes, sulfonamide resistance of Sul2 was observed in 95.5% of the samples and was not seen in 4.5% of the samples. Nitrofurantoin resistance genes in the samples showed that 9.1% of the samples contained nfsa gene and 4.5% contained nfsb gene. Other samples did not have any nitrofurantoin resistance gene. Conclusion: Improper use of antibiotics has caused multidrug resistance to Salmonella, so the study of genes and resistance mechanisms in Salmonella strains isolated from produced eggs in Iran is vital.